2019
DOI: 10.1186/s40425-019-0554-8
|View full text |Cite
|
Sign up to set email alerts
|

HHLA2 in intrahepatic cholangiocarcinoma: an immune checkpoint with prognostic significance and wider expression compared with PD-L1

Abstract: BackgroundIntrahepatic cholangiocarcinoma (ICC) is a highly mortal malignancy with limited therapeutic options. Immunotherapies targeting PD-1/PD-L1 pathway represent a promising treatment for ICC. However, PD-L1 expression and microsatellite instability are not common in ICC. This study aimed to investigate whether HHLA2, a newly identified B7 family immune checkpoint for T cells, could be a therapeutic target next to PD-L1 in ICC.MethodsExpression levels of PD-L1 and HHLA2 as well as infiltrations of CD3+, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
114
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(130 citation statements)
references
References 35 publications
14
114
1
1
Order By: Relevance
“…Low PD-L1 expression is also a major cause of poor PD-1 blocking; accordingly, co-inhibitory receptors are a promising area of research. The newly discovered T cell B7 family immune checkpoint, HHLA2, is a cotherapeutic target for PD-L1, improving the number and activity of T cells in the tumor microenvironment [165]. Another co-inhibitory receptor, KLRG1, expressed on late-differentiated effector cells and CD8 + T and NK cells, is up-regulated in treated tumor samples, resulting in drug resistance; blocking both KLRG1 and PD-1 can improve outcomes [166].…”
Section: Combination Therapeutic Strategy To Enhance T Immune Cell Fumentioning
confidence: 99%
“…Low PD-L1 expression is also a major cause of poor PD-1 blocking; accordingly, co-inhibitory receptors are a promising area of research. The newly discovered T cell B7 family immune checkpoint, HHLA2, is a cotherapeutic target for PD-L1, improving the number and activity of T cells in the tumor microenvironment [165]. Another co-inhibitory receptor, KLRG1, expressed on late-differentiated effector cells and CD8 + T and NK cells, is up-regulated in treated tumor samples, resulting in drug resistance; blocking both KLRG1 and PD-1 can improve outcomes [166].…”
Section: Combination Therapeutic Strategy To Enhance T Immune Cell Fumentioning
confidence: 99%
“…In contrast to that in normal tissues, the protein expression of HHLA2 is widely observed in most of tumor specimens from the colon, breast, lung, thyroid, pancreas, ovary, liver, bladder, prostate, kidney, and esophagus, as well as in melanoma specimens (59). Several studies showed that overexpression of HHLA2 was significantly correlated with poor survival and clinical outcomes in patients with bladder urothelial carcinoma (60), clear cell renal cell carcinoma (61), osteosarcoma (62), and intrahepatic cholangiocarcinoma (63). However, high HHLA2 expression predicts better survival for patients with pancreatic cancer (64) and unresectable advanced or recurrent gastric cancer (65).…”
Section: Human Endogenous Retrovirus-h Long Terminal Repeat-associatimentioning
confidence: 99%
“…In a study on ICC , B7‐H5 was identified as an independent prognostic indicator for OS. B7‐H5 was used as an inhibitory checkpoint and it was found that B7‐H5 expression was more frequent in ICC than PD‐L1 (49·0 versus 28·1%).…”
Section: B7‐h5 Expression In Cancer and Relationship With Cancer Progmentioning
confidence: 99%